Community Health Worker Empowerment and Pregnant Women’s Compliance with the P4K Program in Penfui Timur, Nusa Tenggara Timur - Serlyansie Boimau; Agustina Abuk Seran; Nurlaelah Al Tadom; Wirawati Amin; Andi Syintha Ida (Journal of Public Health Sciences, 2026)
This article reports an analysis of the relationship between the level of cadre empowerment and pregnant women’s compliance with the implementation of the Birth Planning and Complication Prevention Program (P4K). The study employed a cross-sectional survey design conducted in Penfui Timur Village, Kupang Regency, involving 30 community health cadres. Cadre empowerment was assessed through dimensions of knowledge, skills, support, and participation, while pregnant women’s compliance served as the dependent variable. Data were collected using structured questionnaires and analyzed using univariate analysis, bivariate analysis with the Chi-square test, and multivariate analysis using logistic regression. The results showed a significant association between cadre empowerment and pregnant women’s compliance with P4K implementation (p = 0.012). Cadres with a high level of empowerment were more effective in assisting compliant pregnant women compared to those with lower levels of empowerment. Participation in P4K training also had a significant effect on improving pregnant women’s compliance (p = 0.021). These findings indicate that cadre empowerment and training are key factors in enhancing pregnant women’s compliance with the P4K program. Strengthening cadre capacity through continuous training and institutional support is therefore necessary to optimize program implementation at the community level.